Liver Fibrosis Is Associated With Hemorrhagic Transformation in Patients With Acute Ischemic Stroke - Yuan, Cheng-Xiang; Ruan, Yi-Ting; Zeng, Ya-Ying; Cheng, Hao-Ran; Cheng, Qian-Qian; Chen, Yun-Bin; He, Wei-Lei; Huang, Gui-Qian; He, Jin-Cai (Frontiers in Neurology, 2020)
Background: Hemorrhagic transformation (HT) is a frequent, often asymptomatic event that occurs after acute ischaemic stroke (AIS). Liver fibrosis, usually subclinical, is common and crucial in the development of liver disease. We aimed to investigate the association between liver fibrosis and HT in patients with AIS. Methods: We performed a single-center and retrospective study. A total of 185 consecutive participants with HT and 199 age- and sex-matched stroke patients without HT were enrolled in this study. We calculated one validated fibrosis index — Fibrosis-4 (FIB-4) score, to assess the extent of liver fibrosis. HT was detected by routine CT or MRI, and was radiologically classified as hemorrhagic infarction type 1 or 2 or parenchymal hematoma type 1 or 2. HT was also classified into asymptomatic or symptomatic. We used logistic regression models adjusted for previously established risk factors to assess the risks for HT. Results: The median FIB-4 score was significantly higher among patients who developed HT than among those without HT, whereas standard hepatic assays were largely normal. Patients were assigned to groups of high FIB-4 score and low FIB-4 score based on the optimal cutoff value. Compared with the subjects in the low FIB-4 score group, incidence of HT for the high FIB-4 score group was significantly higher. After adjusting for potential confounders, the patients with high FIB-4 score had 3.461-fold of risk of HT in AIS compared to the patients with low FIB-4 score (odds ratio, 3.461 [95% CI, 1.404–8.531]).